1992
DOI: 10.1002/cne.903170305
|View full text |Cite
|
Sign up to set email alerts
|

Galanin‐like innervation of rat submandibular and sublingual salivary glands: Origin and effect on acinar cell membranes

Abstract: The distribution and source of a galanin-like innervation of rat salivary glands has been examined. Additionally, submandibular and sublingual acinar cell membrane responses to galanin or a cholinergic agonist were studied. Galanin-immunoreactive fibers were observed throughout the submandibular and sublingual glands in association with ducts and acini. A subset of submandibular ganglion cells expresses galanin immunoreactivity. Parasympathectomy resulted in a marked decrease in galanin immunoreactivity in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…Our results are in accord with those of Konopka et al (1992) who investigated GAL-like innervation of the rat mandibular and sublingual salivary glands.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results are in accord with those of Konopka et al (1992) who investigated GAL-like innervation of the rat mandibular and sublingual salivary glands.…”
Section: Discussionsupporting
confidence: 93%
“…Experiments utilising retrograde neuronal tracing have demonstrated that GAL-immunoreactive sensory neurons in the trigeminal ganglion do not innervate the madibular ganglion. These results indicate that galanin-like innervation of the rat MGl derives from parasympathetic nerves to the glands (Konopka et al 1992).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…GAL-IR fibers in the rat iris also disappear after lesions of the trigeminal nerve, and are unaffected by extirpation of the SCG (Stro$ mberg et al, 1987). Curiously, GAL is found in only a small percentage of rat TG neurons (Stro$ mberg et al, 1987 ;Suzuki et al, 1989 ;Konopka, May and Forehand, 1992) ; this observation stands in apparent contrast to the high density of GAL-IR sensory nerve fibers seen in the cornea.…”
Section: Corneal Sensory Peptidergic Innervationmentioning
confidence: 59%
“…Thus, in many ways, galanin can be considered a neural peptide. In fact, experimental findings suggest that galanin acts as a neurotransmitter or neuromodulator affecting glandular, nervous, and muscular tissues (Tatemoto et al 1983;Ahrén et al 1988;Vrontakis et al 1991;Konopka et al 1992).…”
Section: Introductionmentioning
confidence: 99%